Aljamiado Hispanofilipino the Spanish language in Philippine Jawi script - Donoso, Isaac (Philippine studies : historical and ethnographic viewpoints, 2018)
"From the seventeenth century to the nineteenth century Philippine Moros increasingly wrote the Spanish language in Arabic script known as Philippine Jawi. This cultural phenomenon, which went beyond mere code switching, is illustrated through documents found in the National ARchives of the Philippines, particularly protocols involving the Tausug and Maguindanao sultanates. The use of Spanish in Jawi documents inclreased, thanks to Zamboanga's role as cultural center in the south and Manila's ability to attract sultans politically. Jawi was also used as the script in language primers through the strategic work of the Jesuit Jacinto Juanmarti, who originated Moro philology."